2020
DOI: 10.3390/plants9111597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Relative Scent Intensity, Volatile Compounds and Gene Expression in Freesia “Shiny Gold”

Abstract: Scent is one of the most important economic traits in Freesia hybrida. “Shiny Gold”, a popular cultivar in South Korea, is widely cultivated for its scent. The relative scent intensity of “Shiny Gold” was approximately 16% higher in full-bloomed flower when compared to the yellow bud stage, while tissue-specifically, tepals showed higher intensity in electronic-nose (e-nose) analysis. E-nose analysis also showed that the scent intensity of “Shiny Gold” was higher and lower than “10C3-424” and “10C3-894”, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These data demonstrated that monoterpenoids and sesquiterpenoids had a significant influence on the floral characteristics of Hedychium accessions. Previous studies also showed that the expression of genes related to the biosynthesis of terpenoids in Anthurium [ 45 ], Lilium ‘Siberia’ [ 29 , 30 , 31 ], and Freesia [ 42 ] had a certain correlation with the volatilization of terpenoids. In the future, the relationship between genes related to the biosynthesis pathway of terpenoids and their volatile compounds will be worth exploring in Hedychium .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data demonstrated that monoterpenoids and sesquiterpenoids had a significant influence on the floral characteristics of Hedychium accessions. Previous studies also showed that the expression of genes related to the biosynthesis of terpenoids in Anthurium [ 45 ], Lilium ‘Siberia’ [ 29 , 30 , 31 ], and Freesia [ 42 ] had a certain correlation with the volatilization of terpenoids. In the future, the relationship between genes related to the biosynthesis pathway of terpenoids and their volatile compounds will be worth exploring in Hedychium .…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectra were obtained by automatic scanning at m/z 20 to 500 amu. The identification of compounds was perceived via comparing the mass spectra with NIST 08 at a match factor of ≥80 [ 42 , 51 ]. The data were processed using mass hunter qualitative analysis workflow software (Agilent Technologies Inc., Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…'Alabama' were studied. The olfactory tests were performed by treated individuals [13]. The results showed that the proportion of fragrant plants of F1 generation from the cross (A.…”
Section: Analysis Of the Key Genes Involved In Volatile Organic Compound (Voc) Biosynthetic Pathwaysmentioning
confidence: 99%
“…To date, VOC profiles have been analyzed in many species, including Dianthus caryophyllus L. [4], Rosa × hybrida [5], Osmanthus fragrans Lour. [6], Freesia [7], Lycoris [8], Gelsemium sempervirens [9], Lilium [10], Chimonanthus praecox [11], Polianthes tuberosa L. [12], Prunus mume [3], and Freesia hybrida [13], amongst others. Although the VOCs emitted by flowers vary greatly among different species, they can be divided into three major groups according to their biosynthesis origins: terpenoids, phenylpropanoids/benzenoids, and fatty acid derivatives [14].…”
Section: Introductionmentioning
confidence: 99%